Analysis of the Accounting Credibility of Garuda Indonesia Financial Transactions with Mahata Aero Teknologi - Girang Permata Gusti; Agnes Bieattant Budianto (Jurnal Manajemen Indonesia, 2020)
This study aims to analyze the feasibility of recording financial statements in 2018 carried out by Garuda Indonesia, specifically transactions conducted by Garuda companies with Mahata. Using descriptive research methods, which include case studies and document review. The results obtained are that the transaction entitlement to the payment commitment by Mahata to the Garuda which is recorded in the other income section is incorrect, that should not be recognized all as other income based on PSAK 23 "revenue", revenue recognition of rights compensation costs should be recognized based on the PSAK 30 "rent". In addition there are indications Mahata's inability to carry out part of it large scope of work and pay fees compensation rights according to the invoice deadline. Keywords—Garuda Indonesia; Mahata;Acrual based; Cash based